Analisis tentang Peran dan Fungsi Kantor Urusan Agama dalam Masalah Wali 'Adhal - Dandi Saputra; Fitra Nelli (Program Studi Magister Hukum Islam - UIN Bukittinggi, 2025)
The purpose of this article is to describe the role of mediation in wali 'adhal (guardianship that prevents) in marriage at the Office of Religious Affairs (KUA). This is because, in the Minister of Religious Affairs Regulation No. 20 of 2019, the Compilation of Islamic Law (KHI), or Law No. 1 of 1974. The KUA often acts as a mediator between the guardian and the prospective bride. The head of the KUA or marriage registrar is obliged to help bring the couple together by mediating between the two parties. If this fails, the case is forwarded to the Religious Court where a substitute guardian can be appointed. This study describes the importance of the KUA's role in defending women's rights through mediation and recommends improving the mediation process and establishing clearer guidelines regarding the KUA's authority in resolving marriage disputes. The method used in this study is descriptive qualitative, looking at existing data in the field and studying relevant literature. The conclusion of this article is that the importance of a persuasive approach in mediation and the delegation of authority to other parties when necessary demonstrates the flexibility of the KUA in meeting the needs of the community. This shows that the role of the KUA in resolving 'adhal guardian cases is not only focused on marriage registration but also includes aspects of mediation, consultation, and appropriate legal action, thereby ensuring the implementation of a valid and harmonious marriage. Tujuan dari artikel ini adalah untuk menggambarkan peran mediasi dalam wali 'adhal (perwalian yang menghalangi) dalam perkawinan di Kantor Urusan Agama (KUA). Hal ini karena, dalam Peraturan Menteri Agama No. 20 Tahun 2019, Kompilasi Hukum Islam (KHI), atau Undang-Undang No. 1 Tahun 1974. KUA sering bertindak sebagai mediator antara wali dan calon pengantin perempuan. Kepala KUA atau Pencatat Nikah berkewajiban untuk membantu mempertemukan pasangan tersebut dengan memediasi antara kedua belah pihak. Jika ini gagal, kasus tersebut diteruskan ke Pengadilan Agama di mana wali pengganti dapat ditunjuk. Penelitian ini menggambarkan pentingnya peran KUA untuk membela hak-hak perempuan melalui mediasi, dan merekomendasikan untuk meningkatkan proses mediasi dan menetapkan pedoman yang lebih jelas yang berkaitan dengan wewenang KUA dalam menyelesaikan sengketa perkawinan.